Approximation by matrix transforms in generalized grand Lebesgue spaces with variable exponent. Issue 4 (12th March 2021) - Testici, Ahmet; Israfilov, Daniyal M.
Abstract : The approximation properties of the matrix transforms, constructed via lower triangular matrices, satisfying some additional conditions, in the generalized grand Lebesgue spaces with variable exponent are studied and the appropriate rates of approximation are estimated.